(3QO GdJTQjOg aj eSFdI GdJbdjOgs - (3CHh GdYHGS CMeO Hf eHGQc Hf eMeO GdSLdeGSj GddeWj,J (B1156 (3g` s ((3CMeO Hf eHGQc Hf eMeO Hf Ydi GdSLdeGSi GddeWi s)
(3ChdgG (B:s
(3GdMeO ddg hMOg SejJgG QO GdJTQjOI ai eSFdI GdJbdjOI EYde Cf eSFdI GdJbdjOI dGjJVM CeQgG Edi HNeSI CehQ CMOgG gd GdJcajQ TQYi Ch Ybdi s
(3BNQgG (B:s
(3hZdHJ GdCghGA Ydi Ybhdge hGSJMhP GdTjWGf Ydi bdhHge hcPdc jWHY Gddg Ydi bdhH GdeYJOjf hgPG BNQ eG bUOJg hbUGQi eG EYJeOJg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B201 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B56s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs